Comparación del índice cintura / estatura y el índice de masa corporal en la determinación del síndrome metabólico en adolescentes - Namoc Leturia, Sisi Melina (2014)
Among children both general and visceral obesity are associated with increased cardiometabolic risk. The increasing prevalence of the metabolic syndrome (MS) in children and adolescents increases cardiovascular risk. Studies of new clinical markers which can easily and accurately predict MS in children and adolescents are needed. Aim: To determinate waist to height ratio (WHR) as predictor of MS in relation rather than the Body Mass Index (BMI) in children from 10 year old to 17th 11 month 29 days of age in the Pediatric consult in the Victor Lazarte Echegaray´s Hospital since December 2012 to May 2014. Method: cross-sectional study in 358 patients. Weight, height, waist circumference, blood pressure, lipid profile and blood glucose was determined. The SM is in the presence of CC> 90th percentile and ≥ 2 ALAD´s criteria. The SM is modeled as a function of BMI percentile and ICE with simple frequency tables and duplicate entries with their absolute and relative frequencies. In addition, diagnostic measures of sensitivity and specificity, and predictive values were estimated validity index for comparison of the prediction of the metabolic syndrome among both anthropometric techniques, with a significance level of 5%. Results: The prevalence of MS was 9.5%. The average BMI of 25.86 ± 3.66 and 0.53 ± 0.06 ICE. The SM was presented at a higher rate in females (55.88%) and obese children (73.52%).The IMC´s sensitivity was 73.53%, specificity 46.3% and ICE´s sensitivity was 100% and specificity 34.88%. The BMI´s validity index was 48.88% and ICE´s was 41.06%. Conclusions: We conclude that ICE is not better predictor for the Metabolic Syndrome than the BMI